Tool Life and Surface Roughness of A390 Aluminum Alloy in Milling Process Under Dry and Cryogenic Conditions - Othman, K.; A.Ghani, J.; Afifah, J.; A.Rahman, H.; H.Haron, C.; S.Amin, N. (International Journal of Engineering and Technology, 2018)
Aluminum alloy is a lightweight material with high strength-to-weight ratio, low thermal expansion, excellent castability and is applied for heavy wear applications. Recent trends in machining research aimed for improving process and product performance by understand the effect of different cooling/lubrication techniques on machining execution. The milling of A390 Al-Si alloy under dry and cryogenic conditions was investigated and liquid nitrogen (LN2) was used as the cryogenic media. The experimental trial were performance with cutting speeds at 250-350 m/min, feed rates at 0.02-0.04 mm/tooth, radial depth of cut at 12.5-25 mm, and the axial depth of cut was kept constant at 0.3 mm using a coated carbide cutting insert. The results outcomes indicate, an application of cryogenic machining had improved the surface roughness, and there was higher tool life as compared to dry cutting condition. The utilization of cryogenic cooling technique had increased the tool life more than 50% and improved the surface roughness more than 40% as compared with dry condition. It is suggested to the machining industry to consider the application of LN2 as the cryogenic media to have better machinability in machining A390 Al-Si alloy.Â Â Â